Network Security Enhancement using CTI and Log Analysis (International Journal of Engineering and Computer Science, 2018)
Cyberattacks, ever increasing in severity, complexity and frequency are impacting the functioning of citizens, government, and businesses around the world. Protecting valuable intellectual property, business and personal information in digital form against theft, misuse, is an increasingly critical concern for everyone in the present digital era. The financial and reputational loss incurred due to Cyber-attacks motivate organizations to improve defensive measures to protect their organizational networks and information stored. This paper proposes an Cyber threat Intelligence (CTI) collection, log analysis and automated Threat alerting platform capable to analyze and respond to incidents that can lead to cyberattacks. The proposed system makes use of CTI received from Open Source intelligence (OSINT), Elasticsearch and Logstash to analyze, observe and generate alerts for malicious traffic/ activity in organization based on log analysis. At the same time an easy to understand visual representation can be made by the use using Kibana.